SAT-349 Cinacalcet Resistant Tertiary Hyperparathyroidism with One Large Parathyroid Gland - Chaker, Bayan (J Endocr Soc, 2020)
Tertiary hyperparathyroidism is thought to develop after long term secondary hyperparathyroidism, such as CKD on dialysis. In This case, all parathyroid glands are significantly enlarged. We report a case of an 84-year-old female with a past medical history of ESRD on HD and recurrent nephrolithiasis who was found to have an enlarged multinodular goiter with the dominant mass in the lower pole of the right gland measuring about 4.7 cm on thyroid ultrasound. Blood work was done which showed elevated intact PTH levels at 2720 pg/mL (12–88). Her calcium level was normal at that time at 10.5 mg/dL (8.6–10.8) with an albumin of 4.2 g/dL (3.5–5.7), and a phosphorus of 5.7 mg/dL (2.5–4.5). Patient had a DEXA scan which showed severe osteoporosis in the lumbar spine, left hip, and right forearm. Patient had increased PTH levels despite being on Cinacalcet. She had a nuclear medicine parathyroid scan with SPECT CT which showed increased uptake along the right inferior thyroid concerning for a large right lower parathyroid adenoma or functional thyroid nodule. FNA of the nodule was done and showed colloid nodule but PTH wash showed elevated PTH at 7634 pg/mL. She was referred for right lower parathyroidectomy and Cinacalcet was discontinued prior to surgery. She had right and left inferior parathyroidectomy and 4 gland exploration. Pathology showed the right inferior parathyroid gland to be markedly hyper-cellular, weighing 36 grams consistent with hyperplasia and the left inferior parathyroid gland to be slightly hyper-cellular parathyroid gland consistent with hyperplasia. No evidence of malignancy was noted on pathology. Prior to surgery her calcium level of 10.6 mg/dL which went down to 9.6 mg/dL post-operatively. Patient then developed severe hypocalcemia and hungry bone syndrome following the surgery requiring a calcium drip for 3 days post-operatively. Was changed to oral calcium but required large amounts of calcium gluconate and calcitriol supplementation and an extended hospital stay of 13 days. However, throughout the hospital stay, PTH levels continued trending back up to 239 which may represent either increased activity from remaining parathyroid glands or residual parathyroid adenoma with incomplete resection. Post-operative US neck showed Post-surgical collection in the lower pole of the right gland measuring 4.8 cm compatible with recent resection. In conclusion, tertiary hyperparathyroidism can develop due to one enlarged parathyroid gland or an adenoma, which can be resistant to cinacalcet.